The Effects of Bud Load and Applied Water Amounts on the Biochemical Composition of the ‘Narince’ Grape Variety (Vitis vinifera L.) - Serpil GOK TANGOLAR; Semih TANGOLAR; Güzin TARIM; Haşim KELEBEK; Sevilay TOPÇU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2015)
This study evaluated the effects of various bud load and water amounts (WA) on the berry composition of the ‘Narince’ white wine grape variety. Two water amounts (WA-I and WA-II) administered during growth stages or a non-irrigated (rain-fed) control treatment were paired with two different bud loads (K (normal) and 2K (two-fold buds) to assess their effects on sugar, organic acid and  phenolic compound contents, as well as antioxidant capacity of the berries for a white wine grape variety ‘Narince’. Despite a slight decrease observed only in sugars in the second year, increases in all phenolic compounds examined (especially in catechin and epicatechin) were detected in the WA-I application. The total phenolic compound values obtained for 2K in the same application was also high. The antioxidant capacity values were not significantly affected by the irrigation or bud load applications. Therefore, a 2K bud load with WA-I treatments in which 50% and 75% of the cumulative evaporation from the Class A pan during berry set to veraison and veraison to ripening, respectively, are recommended for irrigation in high plateau viticulture. By maintaining or increasing the fruit composition of ‘Narince’ grapes, these treatments can optimize grape yield and the earnings of growers. In all applications, glucose (among the sugars), tartaric acid (among the organic acids), and catechin and epicatechin (among the phenolic compounds) were higher than their counterparts.